Upcycling of Belgian endive (Cichorium intybus var. foliosum) by-products. Chemical composition and functional properties of dietary fibre root powders. (1st December 2020) - Twarogowska, Anna; Van Poucke, Christof; Van Droogenbroeck, Bart
Highlights: A dietary fibre concentrate (DFC-BE) from Belgian endive by-products was produced and characterised. The obtained powder was tasteless, low in sugars and rich in insoluble dietary fibres. DFC-BE exhibited excellent hydration properties. DFC-BE presented potential as fibre rich functional ingredient. Abstract: By-products of Belgian endive represent an interesting yet underutilised source of dietary fibre (DF). Dietary fibre concentrates (DFC) that are low in sugar and neutral in taste are sought by the food industry to increase DF content and improve texture in food products. The aim was to set up a biorefinery process to produce DFC from forced roots of Belgian endive (DFC-BE) and characterise the resulting product. As a control, non-treated forced roots powder (FRP-BE) was tested. Water extraction significantly (p < 0.05) decreased the content of sugars, phenolic acids (PA) and sesquiterpene lactones (SL) in DFC-BE. In contrast, total dietary fibre concentration (TDF) was higher in DFC-BE (81.82 g/100 g DW) in comparison to FRP-BE (49.04 g/100 g DW). DFC-BE offers an excellent water holding capacity (WHC) of 14.71 g water/g DW and a swelling capacity (SWC) of 23.46 mL water/g DW, suggesting possible use as a functional food ingredient.